Rotifer Brachionus rotundiformis enriched with taurine for survival and growth of larval milkfish Chanos chanos - Aimma, Muhammad Ariful; Dedi Jusadi; Suprayudi, Muhammad Agus; Alimuddin, Alimuddin; Adiasmara Giri, I Nyoman; Shofa Adestia, Talita (Indonesian Society of Scientific Aquaculture (ISSA), 2025)
This research evaluated the effect of taurine-enriched rotifers on the survival and growth of milkfish larvae. Twenty-five fertilized milkfish eggs were placed in a 250 L cylindrical fiber tank. This study used a completely randomized design with four treatments and five replications. Three days old larvae were given rotifers enriched with taurine at 0, 25, 50, or 75 mg/L. Larvae were cultured until they were 18 days old. The results showed that the taurine content in rotifers was higher in rotifer at 50 mg/L treatment, then decreased at the 75 mg/L treatment. Taurine content in the milkfish larvae aligned with taurine levels in rotifers. Furthermore, the taurine content in rotifers affected milkfish larvae' survival and body length. The highest larval survival and growth was obtained in the 50 mg/L taurine treatment. Thus, it can be concluded that taurine at 50 mg/L is the optimal rotifer enrichment dose for milkfish larvae. Keywords: growth, milkfish larvae, notochord, survival rate, taurine ABSTRAK Penelitian ini dilakukan untuk mengevaluasi pengaruh pemberian rotifera yang diperkaya taurin terhadap kelangsungan hidup dan pertumbuhan larva ikan bandeng. Dua puluh lima butir telur ikan bandeng yang telah dibuahi ditempatkan pada tangki fiber berbentuk silinder berukuran 250 L. Penelitian ini menggunakan rancangan acak lengkap dengan empat perlakuan dan lima ulangan. Larva berumur tiga hari setelah menetas diberi rotifer yang diperkaya taurin dengan dosis 0, 25, 50, atau 75 mg/L. Larva dipelihara hingga berumur 18 hari. Hasil penelitian menunjukkan bahwa kandungan taurin pada rotifer tertinggi diperoleh pada perlakuan rotifer 50 mg/L, kemudian menurun pada perlakuan rotifer 75 mg/L. Kandungan taurin pada larva ikan bandeng sebanding dengan kandungan taurin pada rotifer. Kandungan taurin pada rotifer berpengaruh nyata terhadap kelangsungan hidup dan panjang tubuh larva ikan bandeng. Kelangsungan hidup dan pertumbuhan larva tertinggi diperoleh pada perlakuan dosis 50 mg/L. Dari hasil penelitian dapat disimpulkan bahwa pemberian taurin 50 mg/L pada pengayaan rotifer merupakan dosis yang optimal untuk diberikan pada larva ikan bandeng. Kata Kunci: kelangsungan hidup, larva bandeng, notochord, pertumbuhan, taurin